The effectiveness of the guided inquiry learning model and jigsaw towards students\ Natural Science Outcomes in Grade 4 Elementary school Gugus Pangeran Diponegoro, Demak District - Fika Kurnia Dewi (Tanjong Malim, 2022)
The effectiveness of the guided inquiry learning model and jigsaw towards students\ Natural Science Outcomes in Grade 4 Elementary school Gugus Pangeran Diponegoro, Demak District by Fika Kurnia Dewi